Children's neighbourhood physical environment and early development: an individual child level linked data study. Issue 4 (20th January 2020) - Bell, Megan F; Turrell, Gavin; Beesley, Bridget; Boruff, Bryan; Trapp, Gina; Zubrick, Stephen R; Christian, Hayley E
Abstract : Background: Identification of features of the neighbourhood physical environment that have a causal association with positive child development is important for promoting long-term developmental health. Previous research on these associations have been conducted at the neighbourhood level, and do not account for individual variation in exposure to these features. Methods: This cross-sectional study utilised de-identified linked administrative data. Neighbourhood features were measured with Geographic Information Systems and identified within a 1600 m service area around the child's home address. The study population included a random selection of 5024 Western Australian children who participated in the 2012 Australian Early Development Census (AEDC; median age 5 years, 5 months). Multi-level logistic regressions modelled the odds of children scoring in the bottom 10% on the physical, social or emotional AEDC domains as an outcome of neighbourhood features. Results: After adjustment for individual and neighbourhood sociodemographic factors, lower odds of physical vulnerability were associated with increased neighbourhood residential density, presence of railway station, and higher counts of playgroups and kindergartens. Larger areas of neighbourhood home-yard space were associated with increased odds of physical and social vulnerability. Presence of high-quality green spaces was associated with lower odds of social vulnerability. Increased road traffic exposure was associated with higher odds of social and emotional vulnerability. Conclusions: The neighbourhood physical environment has a weak but significant association with early childhood development. Future research should consider the interplay between the neighbourhood environment and proximal influences, including parenting attributes and socioeconomic status, and how they influence early child development.